Specific deletion of AMP-activated protein kinase (α1AMPK) in mouse Sertoli cells modifies germ cell quality. (5th March 2016) - Bertoldo, Michael J.; Guibert, Edith; Faure, Melanie; Guillou, Florian; Ramé, Christelle; Nadal-Desbarats, Lydie; Foretz, Marc; Viollet, Benoit; Dupont, Joëlle; Froment, Pascal
Abstract: The AMP-activated protein kinase (AMPK) is an important regulator of cellular energy homeostasis which plays a role in fertility. Complete disruption of the AMPK catalytic subunit α1 gene (α1AMPK KO) in male mice results in a decrease in litter size which is associated with the production of altered sperm morphology and motility. Because of the importance of Sertoli cells in the formation of germ cells, we have chosen to selectively disrupt α1AMPK only in the Sertoli cells in mice (Sc-α1AMPK-KO mice). Specific deletion of the α1AMPK gene in Sertoli cells resulted in a 25% reduction in male fertility associated with abnormal spermatozoa with a thin head. No clear alterations in testis morphology or modification in the number of Sertoli cells in vivo were observed, but a dysregulation in energy metabolism in Sertoli cells occurred. We have reported an increase in lactate production, in lipid droplets, and a reduction in ATP production in Sc-α1AMPK-KO Sertoli cells. These perturbations were associated with lower expression of mitochondrial markers (cytochrome c and PGC1 -α ). In addition another metabolic sensor, the deacetylase SIRT1, had a reduction in expression which is correlated with a decline in deacetylase activity. Finally, expression and localization of junctions forming the blood-testis barrier between Sertoli cells themselves and with germ cells were deregulated in Sc-α1AMPK-KO. In conclusion, these results suggest that dysregulation of the energy sensing machinery exclusively through disruption of α1AMPK in Sertoli cells translates to a reduction in the quality of germ cells and fertility. Highlights: Specific deletion of the α1AMPK gene in Sertoli cells resulted in a 25% reduction in male fertility. The reduction in fertility was associated with abnormal sperm with a thin head. Sertoli cells lacking the α1AMPK subunit had dysregulated energy metabolism with altered lactate, lipid and ATP production. The expression of the metabolic sensor SIRT1 was reduced in mutant cells. α1AMPK plays a role in junctional protein expression and localization in Sertoli Cells.